Isocitrate dehydrogenase 1 mutation sensitizes intrahepatic cholangiocarcinoma to the BET inhibitor JQ1. Issue 11 (17th September 2018) - Fujiwara, Hiroaki; Tateishi, Keisuke; Kato, Hiroyuki; Nakatsuka, Takuma; Yamamoto, Keisuke; Tanaka, Yasuo; Ijichi, Hideaki; Takahara, Naminatsu; Mizuno, Suguru; Kogure, Hirofumi; Matsubara, Saburo; Nakai, Yousuke; et al.
Abstract: Cholangiocarcinoma is a life‐threatening disease with a poor prognosis. Although genome analysis unraveled some genetic mutation profiles in cholangiocarcinoma, it remains unknown whether such genetic abnormalities relate to the effects of anticancer drugs. Mutations in isocitrate dehydrogenase 1 and 2 ( IDH1/2 ) are exclusively found in almost 20% of intrahepatic cholangiocarcinoma (ICC). Recently, the anticancer effects of BET inhibitors including JQ1 have been shown in various tumors. In the present study, we report that the antigrowth effect of JQ1 differs among ICC cells and IDH1 mutation sensitizes ICC cells to JQ1. RBE cells harboring IDH1 mutation was more sensitive to JQ1 than HuCCT1 or HuH28 cells with wild‐type IDH1 . JQ1 induced apoptosis only in RBE cells through the upregulation of proapoptotic genes BAX and BIM . We found that the antigrowth effect was not attributed to downregulation of the MYC gene as a well‐known target of JQ1 in various cancer cells. Notably, the forced expression of mutant IDH1 successfully sensitized HuCCT1 cells to JQ1. In addition, AGI‐5198, a selective inhibitor of mutant IDH1 partially reversed the decrease in viability after JQ1 treatment and also suppressed the JQ1‐induced apoptosis in RBE cells. These data suggest that IDH1 mutation contributed to the growth inhibitory effect of JQ1 in RBE cells. Furthermore, given that the effect of mutant IDH1 was not recapitulated in glioblastoma cells, the enhancement of JQ1 sensitivity by IDH1 mutation seems to be specific for ICC cells. Our findings propose a new stratified therapeutic strategy based on IDH1 mutation in ICC. Abstract : Mutation of isocitrate dehydrogenase 1 (IDH1) enhanced the sensitivity of JQ1 in intrahepatic cholangiocarcinoma (ICC) cells through the induction of apoptosis. Our findings propose a new stratified therapeutic strategy based on IDH1 mutation in ICC.